(untitled) (Journal of the College of Basic Education, 2022)
Political negotiations took place between Egypt and Britain for more than a year and a half (March 1950 - July 1951), during which the role of Muhammad Salahuddin Othman clearly emerged in these negotiations as the Egyptian Foreign Minister and a representative of the Egyptian side in the negotiation, which adhered to the principle of the unity of the Nile Valley and the British evacuation from Egypt The length of the negotiations, and as his legal efforts to reformulate the 1953 constitution in Egypt emerged, he must be assigned to be a member of the Constitution Evaluation Committee.